Morphology and molecular phylogeny reveal one new species of Hydnellum (Thelephorales) from Eastern China - Fan, Xiang-Ping; Song, Chang-Ge; Xu, Yi-Hua; Sun, Yi-Fei; Cui, Bao-Kai (Phytotaxa, 2025)
As ectomycorrhizal fungi, the species in Hydnellum can form a mutualistic symbiosis with plant roots to promote the restoration of forest vegetation and the stability of forest ecosystems. Some Hydnellum fungi also have edible and medicinal values generating considerable economic benefits. In this study, a new species of Hydnellum collected from Hangzhou, eastern China, was described by utilizing morphological and phylogenetic analyses. Morphologically, Hydnellum hangzhouense was characterized by its light-colored and relatively thick pileus, simple septated generative hyphae, and subglobose to ellipsoid basidiospores. The phylogenetic analysis was conducted based on the combined sequences dataset (ITS + nLSU + nSSU + rpb2). The results indicated that H. hangzhouense formed an independent lineage which is closely related to H. crassipileatum and H. chocolatum. The detailed description, illustrations and phylogenetic tree for demonstrating the taxonomic positions of H. hangzhouense were provided.